2009
DOI: 10.1016/j.exer.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Corneal epithelial proliferation and thickness in a mouse model of dry eye

Abstract: Although several studies have previously focused on the conjunctival epithelial response to surface dryness, little is known about the effect of a dry environment on corneal epithelium, which is the most clinically significant tissue affected in dry eye. The aim of this study was to quantitatively evaluate the effect of desiccating stress on the number of proliferating corneal epithelial cells and corneal epithelial thickness in mice placed in a controlled-environment chamber (CEC) that induces dry eye.Corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 28 publications
4
57
0
1
Order By: Relevance
“…19,20 MGD patients were characterized by extensive MG dropout, MG secretion that could not be expressed, tear film instability, and ocular surface epithelial damage. According to recent literature, [12][13][14] LSCM in these patients showed increased diameters of acinar units and orifices and highreflective secretion.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 MGD patients were characterized by extensive MG dropout, MG secretion that could not be expressed, tear film instability, and ocular surface epithelial damage. According to recent literature, [12][13][14] LSCM in these patients showed increased diameters of acinar units and orifices and highreflective secretion.…”
Section: Discussionmentioning
confidence: 99%
“…12 With the benefit of noncontact, accuracy, stability, and repeatability, OCT was widely used in various studies. 2831 Fabiani et al 9 figured out that the CET became thicker in 7 days after the establishment of DED in a rat model, indicating that epithelial proliferation has a significant impact on the inflammatory process. Kanellopoulos and Asimellis 32 observed augmented epithelial thickness in dry eye patients, whereas Erdelyi et al 33 examined clinical patients and revealed that the CET tends to be thinner in dry eyes, and attributed it to the destruction of stem cells at the limbus.…”
Section: Discussionmentioning
confidence: 99%
“…7 To figure out the morphological evidence of epithelial damage, various studies have been conducted to map the thickness of corneal epithelium. 8,9 Brush cytology, 10 impression cytology, 11 ultrasound, 12 and in vivo confocal microscopy 13 are classical techniques in assessing the epithelial thickness. However, these methods require direct or indirect contact between the instruments and the patient's ocular surface.…”
mentioning
confidence: 99%
“…Dry eye disease increases epithelial cell density and thickness, decreases epithelial cell size, and increases epithelial cell turnover. 1516 Inflammation of the ocular surface is intimately linked to this epithelial dysfunction. The proinflammatory cytokines IL-1 and IFN-γ cause squamous metaplasia of ocular surface epithelial cells, and IFN-γ decreases goblet cell differentiation.…”
Section: Immunopathogenesis Of Dry Eyementioning
confidence: 99%